Static and dynamic graphs modeling of a boiler system / Noor Ainy Harish - Harish, Noor Ainy (Institute of Graduate Studies, UiTM, 2015)
Fuzzy State Space Model (FSSM) is a novel inverse modeling technique used for optimization of input parameters in multivariable dynamic systems whereby the uncertainty of the parameters is considered and incorporated with the crisp state space models proposed in the modern control theory. The model is succesfully implemented to the state space model of a furnace system of a combined cycle power plant. In this study, FSSM is further implemented to the other state space model of a subsystem in the boiler namely superheater, reheater, riser and drum. Since graph theory is rich in theoretical results especially for studying interconnection among elements in natural and man-made system, therefore, graph representing FSSM is initially developed which is based on the graph theoretic approach. However, the graph of FSSM is found to be a static graph where not much analysis of the graph could explain the model of FSSM of a boiler...